Patient and Clinician Perceptions of Informed Consent and Decision Making About Accepting KDPI > 85 Kidneys. Issue 1 (January 2022) - Schantz, Karolina; Gordon, Elisa J.; Lee, Unsun; Rocha, Maria; Friedewald, John; Ladner, Daniela P.; Becker, Yolanda; Formica, Richard; Reese, Peter P.; Kaufman, Dixon; Barah, Masoud; Walker, Marissa; et al.
Abstract : Background: Although the impact of the kidney donor profile index (KDPI) on kidney discard is well researched, less is known about how patients make decisions about whether to give consent for KDPI > 85 kidney offers. Methods: We conducted in-depth, semistructured interviews with 16 transplant recipients, 15 transplant candidates, and 23 clinicians (transplant surgeons, nephrologists, and nurse coordinators) to assess and compare perceptions of transplant education, informed consent for KDPI > 85 kidneys‚ and the decision-making process for accepting kidney offers. Thematic analysis was used to analyze qualitative data. Results: Four themes emerged: (1) patients reported uncertainty about the meaning of KDPI or could not recall information about KDPI; (2) patients reported uncertainty about their KDPI > 85 consent status and a limited role in KDPI > 85 consent decision making; (3) patients' reported willingness to consider KDPI > 85 kidneys depended on their age, health status, and experiences with dialysis, and thus it changed over time; (4) patients' underestimated the survival benefit of transplantation compared with dialysis, which could affect their KDPI > 85 consent decision making. Conclusions: To better support patients' informed decision making about accepting KDPI > 85 kidneys, centers must ensure that all patients receive education about the trade-offs between accepting a KDPI > 85 kidney and remaining on dialysis. Additionally, education about KDPI and discussions about informed consent for KDPI > 85 kidneys must be repeated at multiple time points while patients are on the waiting list. Abstract : Supplemental Digital Content is available in the text.